2018
DOI: 10.1002/phar.2087
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Clinical Utility of the hERG IC50:Cmax Ratio to Determine the Risk of Drug‐Induced Torsades de Pointes: A Meta‐Analysis

Abstract: The hERG IC50:C ratio was correlated with TdP incidence for culprit drugs. This validation provides support for the potential use of the hERG IC50:C ratio for clinical decision making in instances of drug selection where TdP risk is a concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…On the other hand, several drugs in clinical use (among those are antihistamines, fluoroquinolone antibiotics, antipsychotics, antiepileptics) exert off-target inhibitory effects on hERG1 partially with submicromolar IC 50 s but are "non-torsadogenic." One might assume that clinically achieved steady state free plasma concentrations of these "non-torsadogenic" hERG1 inhibitors remain far below its IC 50 concentration for hERG1 (Lehmann et al, 2018). Another explanation for the "non-torsadogenicity" of these drugs is that hERG1 inhibition alone is not sufficient to induce fatal arrhythmia, and the "torsadogenic" action of a certain drug depends on the full spectrum of ion channels that is modulated by the drug [for commentary see (Arcangeli and Becchetti, 2017)].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several drugs in clinical use (among those are antihistamines, fluoroquinolone antibiotics, antipsychotics, antiepileptics) exert off-target inhibitory effects on hERG1 partially with submicromolar IC 50 s but are "non-torsadogenic." One might assume that clinically achieved steady state free plasma concentrations of these "non-torsadogenic" hERG1 inhibitors remain far below its IC 50 concentration for hERG1 (Lehmann et al, 2018). Another explanation for the "non-torsadogenicity" of these drugs is that hERG1 inhibition alone is not sufficient to induce fatal arrhythmia, and the "torsadogenic" action of a certain drug depends on the full spectrum of ion channels that is modulated by the drug [for commentary see (Arcangeli and Becchetti, 2017)].…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Highly selective binding for the D 2 receptors makes olanzapine an attractive option for patients in whom there is a concern for QT prolongation chosen due to its low binding affinity for the I kr channel. 19 In addition, in a meta-analysis to validate the clinical utility of the ratio of the half-maximum inhibition concentration of the hERG channel (hERG IC50) to the peak serum concentration of unbound drug (C max ), Lehmann et al 20 reported that olanzapine is the antipsychotic with the least risk of drug-induced torsade de pointes. Although olanzapine is only approved parenterally for IM use, evidence suggests that IV use may be safe.…”
Section: Discussionmentioning
confidence: 99%
“…Since it is hard to determine the hERG liability of a drug based on the IC 50 value alone, 35 without the knowledge of the peak serum concentration unbound to plasma proteins, we use both activity thresholds (1M and 10 M) to classify the drugs as blockers and non-blockers. Recent progress in deep learning facilitates the development of the different molecular representations such as latent vectors that are used as descriptors for modeling molecular properties.…”
Section: Methodsmentioning
confidence: 99%